(untitled) - Goodrich, Michael T.; Michael T. Goodrich; Roberto Tamassia (Hoboken, NJ)
Fundamental data structures in a consistent object-oriented framework. Now revised to reflect the innovations of Java 5.0, Goodrich and Tamassia's Fourth Edition of Data Structures and Algorithms in Java continues to offer accessible coverage of fundamental data structures, using a consistent object-oriented framework. The authors provide intuition, description, and analysis of fundamental data structures and algorithms. Numerous illustrations, web-based animations, and simplified mathematical analyses justify important analytical concepts
Keywords: Java (Computer program language); Java (Computer program language); Computer algorithms